2017
DOI: 10.1007/s00268-017-4159-4
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Detachable Magnetic Nerve Stimulator for Intraoperative Neuromonitoring

Abstract: The application of stimulating dissection using a detachable magnetic nerve stimulator during thyroidectomy with IONM is simple, convenient, and effective. It provides surgeons with real-time feedback of the EMG response during intermittent IONM. We propose that this novel device could be an essential guide for most surgeons, especially for less experienced head and neck surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Another recent study introduced a detachable magnetic stimulator which could be attached to any metallic surgical instrument. is study also reported comparable nerve stimulation amplitudes between the detachable magnetic stimulator and a conventional stimulator [18]. e ARS is advantageous during the thyroid surgery in terms of time saving.…”
Section: Discussionsupporting
confidence: 51%
“…Another recent study introduced a detachable magnetic stimulator which could be attached to any metallic surgical instrument. is study also reported comparable nerve stimulation amplitudes between the detachable magnetic stimulator and a conventional stimulator [18]. e ARS is advantageous during the thyroid surgery in terms of time saving.…”
Section: Discussionsupporting
confidence: 51%
“…There are some limitations on stimulating side and recording side during thyroid surgery under IONM. To overcome the problems of the stimulation side, the continuous IONM system was introduced [6], and attempts were made to connect the nerve stimulator with the surgical instrument [18-20]. But, there were few attempts to overcome the disadvantages of recording side like EMG during thyroid surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional IONM is comprised of stimulation side and recording side. Recently, several new devices have been reported to overcome the disadvantages of IONM stimulation side [ 8 - 10 ]; moreover, several limitations of IONM recording side when performing electromyography (EMG) on the vocalis muscle, have been reported. First, it was reported that malposition of endotracheal surface electrodes occurs in 3.8% to 23% of the patients [ 11 - 13 ].…”
Section: Introductionmentioning
confidence: 99%